Fatigue in Multiple Sclerosis - Christian Dettmers (Frontiers Research Topics, 2016)
Dear Readers, If you are engaged in the treatment of patients with MS (pwMS), this e-book's aim is to offer novel insights to improve on an understanding of one of the major problems of pwMS: fatigue. Although there is increasing research into fatigue and its impact on MS, this collection of ten articles supports a better understanding of fatigue in MS patients. It explores pathophysiological concepts, provoking mechanisms, objective measurements, personality interactions, pharmacological and non-pharmacological interventions and summarizes clinical management. It is written by neurologists, psychologists, scientists and therapists and addresses this group of people, who deal with pwMS in private, clinical, rehabilitation or scientific settings. Its aim is to communicate high-quality information, knowledge and experience on MS to healthcare professionals, while providing global support for the international MS community.